AB0344 Does the presence of ild influence the choice of dmard and biologic therapy in rheumatoid arthritis?. (12th June 2018) - Coath, F.; Siddiqui, S.; Himashi, A.; Bharadwaj, A.; Dubey, S.; Hayes, F.; Koduri, G.
Abstract : Background: Interstitial lung disease (ILD) is a progressive fibrotic disease of the lung parenchyma. It is the only complication of rheumatoid arthritis (RA) reported to be increasing, accounting for around 7% of all RA deaths. 1 Prognosis of patients with RA-ILD is reported to be poor, with usual interstitial pneumonia (UIP) being the predominant pattern associated with poor survival. 2 It is a challenge to determine specific pattern of ILD and formulate an appropriate treatment plan to achieve stabilisation. Early use of Methotrexate (MTX) and biologics in RA has improved outcomes and quality of life. However, this causes difficulty when RA patients develop ILD. There are reports of ILD with biologics and DMARDs, although it is difficult to establish a causal relationship or if an exacerbation of pre-existing ILD. There are no evidence based guidelines regarding introducing biologics in such patients and clinicians face a dilemma as to whether they should be denied. Objectives: The aim of this retrospective study is to: Check the overall management of RA and ILD. Examine whether ILD diagnosis influences treatment of RA. Methods: We reviewed 37 patients with RA-ILD from 3 hospitals (2001–2017). We collected data on demographics, clinical, Pulmonary function tests, imaging, time from diagnosis to treatment and outcomes. Results: The majority developed ILD after RA except for 3 patients. Mean age of onset of RA was 67 years, 22 (60%) were female. 32 (87%) were RF or ACPA positive, 25 (68%) patients smoked. 29 (78%) patients had baseline PFTs. HRCT showed 13 had NSIP, 20 UIP and 4 were unclassified. Following the diagnosis of ILD, MTX was stopped in 16 patients, reduced in 3 and unchanged in 2. Leflunomide was stopped in 4 and SLZ stopped in 4, of which 1 had definite alveolitis. Infliximab was stopped in 2 patients. Specific Treatment for ILD: 12 patients received Rituximab, of those 8 were for ILD and 4 for RA. 4 Patients continued Anti-TNF. 26 patients received steroids, 4 received MMF and 2 Cyclophosphamide. 2 received Abatacept for ILD with active RA and one received Etanercept. 3 were on Carbocysteine, 2 on NAC and 3 on oxygen. Outcomes: 20 ILD patients were stable and 8 (21%) progressed and died despite treatment. RA disease activity was low to moderate in 23 patients. RA progressed in 8 patients and 1 who received Etanercept was in remission. MTX was stopped in the majority of patients. Steroids were the commonest treatment for RA in the presence of ILD. Rituximab was the drug of choice for RA with severe ILD, followed by MMF and Cyclophosphamide. DMARDs such as HCQ, Leflunomide and SLZ were used for RA in milder ILD and biologics were generally avoided. Conclusions: There appears to be significant variation in the treatment of RA in the presence of ILD. However Rituximab seems to be the prefered option for severe ILD. There is a need for stratified and standardised guidance for management of RA-ILD. References: [1] Bongartz T, Nannini C, Medina-Velasquez YF, et al. Incidence and mortality of interstitial lung disease in rheumatoid arthritis: a population-based study. Arthritis Rheum2010;62:1583–1591. [2] Solomon JJ, Ryu JH, Tazelaar HD, et al. Fibrosing interstitial pneumonia predicts survival in patients with rheumatoid arthritis-associated interstitial lung disease (RA-ILD). Respir Med2013;107:1247–1252. Disclosure of Interest: None declared